2016
DOI: 10.1039/c5sc03992d
|View full text |Cite
|
Sign up to set email alerts
|

A novel probe based on phenylboronic acid functionalized carbon nanotubes for ultrasensitive carbohydrate determination in biofluids and semi-solid biotissues

Abstract: An ultrasensitive SPME probe based on phenylboronic acid functionalized CNTs is applied for direct in vitro or in vivo recognition of carbohydrates in biofluids as well as semi-solid biotissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Given the desirable recognition capacity of OSI‐MNPs and the rapid allochroic feature of PBA‐AGO, the potential of AGO‐OSI for glycoprotein assay was then examined. We noted that the lewis acid‐like boronic acid groups were able to rapidly incorporate proteins through boronate‐affinity chemistry, including the covalent affinity (between boronic acid groups and cis‐diols unites within the glycoproteins) and the B–N interactions (between boronic acid groups and the N‐terminal of the proteins) . Thus, it is reasonable to suppose that PBA‐AGO could efficiently label target glycoproteins via boronate‐affinity chemistry, forming a OSI‐MNPs/glycoproteins/PBA‐AGO sandwich assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Given the desirable recognition capacity of OSI‐MNPs and the rapid allochroic feature of PBA‐AGO, the potential of AGO‐OSI for glycoprotein assay was then examined. We noted that the lewis acid‐like boronic acid groups were able to rapidly incorporate proteins through boronate‐affinity chemistry, including the covalent affinity (between boronic acid groups and cis‐diols unites within the glycoproteins) and the B–N interactions (between boronic acid groups and the N‐terminal of the proteins) . Thus, it is reasonable to suppose that PBA‐AGO could efficiently label target glycoproteins via boronate‐affinity chemistry, forming a OSI‐MNPs/glycoproteins/PBA‐AGO sandwich assembly.…”
Section: Resultsmentioning
confidence: 99%
“…A clear chromatogram profile ( Figure 4B)w ith as trong glucose peak was observed owing to the high selectivity and excellent tolerance of the BA-MIPsp robe.F or comparison, av ery complex chromatogram profile was observed using ar ecently reported biocompatible carbohydrate probe, due to the interference of other saccharides as well as other unwanted species from aloe leaf. [17] Furthermore, MALDI-TOF MS analysis demonstrated that glucose was captured ( Figure 4C)w hile no macromolecules were extracted, which confirmed the good biocompatibility of the BA-MIPs probe ( Figure S13). Finally,t he BA-MIPs probe was used for low-destructivea nd long-term in vivo continuous glucosemonitoringi na loe leaf ( Figure 4D).…”
mentioning
confidence: 75%
“…The need for representative information regarding the actual composition and the dynamics of xenobiotics and biomolecules in plants has led to the development of a variety of in vivo analytical and extraction methods. Compared with other sampling techniques like microdialysis, in vivo tissue collection and biosensors, SPME offers the advantage of a low cost and simple device [44,71,[73][74][75]. This technique allows the efficient and non-exhaustive extraction of the analytes by inserting the fiber directly in plant tissues with minimum disturbance of the living system.…”
Section: In Vivo Spme Extraction Of Plant Tissuesmentioning
confidence: 99%
“…Along with xenobiotics, phytohormones and carbohydrates represent other two important classes of analytes of biological interest. Such endogenous compounds are involved in a variety of regulation and pathological processes [72,75].…”
Section: In Vivo Spme Extraction Of Plant Tissuesmentioning
confidence: 99%